SEM PLS ANALYSIS EFFECT OF MORALE AND COMPENSATION ON ACADEMIC PERFORMANCE (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
The purpose of the study was to examine the effect of morale and compensation on academy performance with organizational culture as a mediationvariable. The population and sample of this study throughout the academy at Siteba Health Polytechnic with sampling techniques using a total sampling technique of 46 people. The results of this study show that (1). Variable morale and compensation have a direct and significant effect on organizational culture. (2) Morale, compensation and organizational culture have a positive and significant effect on academic performance. (3) The mediation effect of organizational variables was found to affect morale and compensation for academic performance